Law and Art in China : Domination and Resistance - Potter, Pitman (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 2017)
The relationship between law and art in contemporary China reveals tensions between dynamics of domination and resistance. On the one hand, law plays a control function in the recognition and protection of private and public property, and in the enforcement of regime interests in controlling expression. By delineating the terms and processes for protecting ownership and conservation of art, China’s legal regime formalizes the scope and boundaries — the very identity — of the art being protected. Law’s domination is also evident in its function to restrict artistic expression. Law in China has long been used to prevent and punish artistic expression with which the ruling regime disagrees. Juxtaposed to the formal domination by law over identity and content, is art’s potential to offer critical insight on China’s legal system. Through this dynamic of resistance, art in China offers perspectives through which to interrogate particular elements of the PRC legal system. This paper will examine these dimensions of art and law in China.